Exploring ELT Students’ Perception of Mobile Phone through Figurative Language - Müfit Şenel (Sakarya University Journal of Education)
The aim of this study is to investigate, analyze and evaluate the mobile phone perceptions of ELT students by the help of figurative language. The participants of this study are Grade 3 and Grade 4 students of ELT Department at Samsun 19 Mayıs University, Faculty of Education, involving 139 students in total. In this research students were asked to use “simile” as a figurative language and complete the sentence “Mobile phone is as ……as…….” in the target language. According to content analysis, the results showed that only 119 of 139 students produced valid sentences, completing sentences considering their social environments and their daily lives. According to the classification of the sentences depending upon the responses of the students, five conceptual categories were identified. At the end of the study, students were found to have both positive and negative concepts about mobile phones; for instance25.2% developed figurative language for ‘part of life’, 18.5% for ‘addiction’, 17.6% for ‘entertainment’, 31.1% for ‘useful device’ and 7.6% for ‘dangerous factor’ categories. Implications are given and suggestions made for language teachers at the end. Most of these results indicate that students’ preferences change depending upon whether they benefit from the use of mobile phones.